Analysis of Liquidity Risk in Chinese Commercial Banks under Basel III - CHEN, BINGJIE (2014)
From American subprime crisis to European debt crisis, the problem of liquidity risk in commercial banks is never out of the public’s sight. At each financial crisis, banks are the first to get into a dilemma. Due to the implicit government guarantee and a macro-economic liquidity surplus, Chinese banking system has experienced a relatively small number of bankruptcy and liquidity crises, which makes it not urgent to manage liquidity risk. However, the 2013 June Currency Shortage in China exposes the severe potential liquidity difficulties. Therefore, this dissertation aims to study current status of liquidity risk and liquidity risk management in Chinese banking system in the post-crisis era. Through the analysis of a series of static indicators, such as the non-performing loan ratio, the loan-to-deposit ratio and the liquidity ratio, it is believed that Chinese commercial banks are still in a condition of excessive liquidity. However, under the influences of new features in financial operation, such as financial disintermediation, inter-bank transaction and off-balance-sheet business, the liquidity risk exposure in Chinese commercial banks enlarges. Additionally, through empirical study of determinants of the liquidity risk in Chinese commercial banks, it can be estimated that the liquidity risk in Chinese commercial banks is generally under greater role by internal factors than by external ones. Banks’ asset size and profitability replenish the liquidity to withstand risks, while higher equity-to-assets ratio and non-performing loan ratio intensify the risk exposure. Banks which have implemented Basel III standards face less likelihood of liquidity risk exposure than banks which have not implemented. After analysing the differences between Basel III and Chinese regulatory rules and differences in the liquidity risk management modes between other countries and China, it can be concluded that the diversified, hierarchical and elaborated tendency of liquidity risk management and regulation in China is necessary.